Communication Education in Indonesia-Timor Leste Border Schools in Building Ecological Awareness and National Resilience - Florens Maxi Un Bria; Vinsensius Bawa Toron; Joel C. Sagut (Studies in Learning and Teaching, 2026)
This study aims to conduct and observe the implementation of communication education in schools in the Indonesia-Timor Leste border area, as well as analyze its influence on the formation of students' ecological awareness in strengthening national resilience and national defense attitudes, and can contribute to the development of communication education models based on ecological and national values in border areas. This study used a qualitative approach with a case study design where three selected schools are Surya Catholic High School in Timor’s capital city, Dili. The number of participants in this study was thirty, including school administrators, teaching staff, and their students. Data were collected by observations and in-depth interviews and analyzed using a qualitative approach, which is data reduction, data display, and conclusion drawing (triangulation). The learning interaction model of dialogical and participatory fostered the contextual learning related to environmental ecology and the incorporation of national values and morality in the community life. The studies are innovative for their approach in integrating communication education, ecological awareness, and national resilience in socio-cultural field border area schools and contextual and participative learning processes.